Pirate queens : dauntless women who dared to rule the high seas - Lewis, Leigh (National Geographic, 2022)
"A collection of fact-filled profiles, poetry, and illustrations of women pirates who made their mark on the high seas. Each profile includes an original poem presented against a backdrop of full-color art by illustrator Sara Woolley Gomez. The profile is followed by information about the real life and times of these daring women"--